GAYA BAHASA ARTIS DALAM MEDIA SOSIAL - Hani Dia Lestari; Nusarini Nusarini (CARAKA, 2017)
This study aims to describe: (1) the type of Language style and (2) the function of the artist language style used in social media. This type of this study is qualitative descriptive. The data is a sentence in the artist status in social media that contains the type of language style and function language style. Data obtained from the language that used an artist in social media. The technique of collecting data is method refer by using the free conversation and note techniques. Methods of data analysis are a unified orthographic method, whereas basic methods such as the method of sorting technique and match certain elements.  The presentation method of the data is informal techniques. The study result on artist status in social media is as follows. 1 the type of  language style that used the artist in social media is as following: (a) the language style affirmation consisting  of:  (1)  aferesis  (2)  alonim  (3)  simploke  (4)  bombastis  (5)  esklamasio  (6) invocation (7 ) anaphora, (b) the comparisons language style which consists of: (1) allusion (2) antonomasia (3) hyperbole (4) litotes (5) personification (6) simile, (c) the opposition language style consisting of: (1) paradox (2) kontradiksio, (d) the satire language style satire consisting of: (1) irony (2) wordplay (3) sarcasm (4) cynicism, 2 the language function style that used the artist in social media include the following: ( a) the language style used to create a state of inner feelings, such as happy, sad and angry (b) the language style is used as a tool to influence and convince the reader or listener (c) the language style serves as a tool to reinforce the effect of the ideas presented.